Optimization of the Utilization of Idle Gas Turbine Generator Assets Using the AHP Method To Reduce Co? Emissions and Improve Operational Efficiency at the CPPG Power Plant of PT ABC - Mochamat Dwi Sutrisno; Ruri Agung Wahyuono (International Journal Labs, 2026)
Gas turbine generator (GTG) assets in upstream oil and gas facilities play an important role in ensuring a continuous power supply for production processes. However, aging equipment, declining reliability, increasing maintenance costs, and limited spare parts availability have become major challenges in maintaining operational efficiency. Meanwhile, the utilization of idle assets provides an opportunity to optimize existing resources, reduce the need for new investments, and support emission reduction targets. This study aims to determine the most suitable alternative for utilizing idle GTG assets at the CPPG Power Plant of PT ABC by integrating technical, economic, operational, policy, and environmental considerations. The research employed a case study approach using the Analytical Hierarchy Process (AHP) method. Data were collected through field observations, technical interviews, focus group discussions, operational documents, maintenance records, cost assessments, fuel consumption data, and expert judgments from ten subject matter experts. The results showed that technical criteria had the highest priority weight of 0.317, followed by economic criteria (0.259), operability criteria (0.189), environmental criteria (0.138), and policy criteria (0.096). The AHP synthesis identified AL3, which involved the relocation of two GTGs from Field T and one GTG from Field L, as the optimal alternative with a priority value of 0.391. This alternative provides an 11 MW output capacity, the lowest estimated maintenance and operational cost of USD 48.04 million, and the highest potential reduction in fuel consumption by 1.05 MMSCFD and CO?e emissions by approximately 22,574 tons/year. In conclusion, the AHP-based decision model effectively supports strategic idle asset utilization decisions by balancing operational reliability, economic efficiency, and environmental sustainability.